A 1–5 GHz 22 mW receiver frontend with active‐feedback baseband and voltage‐commutating mixers in 65 nm CMOS. Issue 7 (15th June 2022) - Guo, Benqing; Wang, Haishi; Wang, Huifen; Li, Lei; Zhou, Wanting; Jalali, Kianoosh
Abstract: A CMOS baseband‐active‐feedback receiver frontend with passive voltage‐commutating mixers is proposed. The active feedback baseband enables in‐band signal amplification and out‐of‐band blocker interference suppression by constructing the RF bandpass filter and BB lowpass filter, simultaneously. The voltage‐commutating mixers embedded in current mirrors significantly reduce the power requirement for the LO generator. The stacked n/pMOS structure is commonly adopted to further improve power efficiency. The receiver frontend is designed in a standard 65 nm CMOS process. Simulation results display an NF of 3.4 dB and a maximum gain of 32 dB from 1 to 5 GHz LO frequency range. The obtained in‐band and out‐of‐band IIP3 are −12 dBm and 9 dBm, respectively. The receiver frontend core only consumes 22 mW at 1 GHz LO frequency and occupies the area of 645 × 543 μm 2, which is suitable for the low‐power application of handheld terminals.